The influence of Mediterranean modernist movement of architecture in Lefkosa: The first and early second half of 20th century - Salar Salah Muhy Al-Din (Alanya Hamdullah Emin Paşa Üniversitesi, 2017)
The twentieth-century modern architectures in Lefkosia in North Cyprus are changing especially in residential building. This change is occurs based on the client’s orders or because of the dilapidated condition of the buildings. Identify the characteristics of modernist architectural movement will help in identifying these buildings and recognize the changes applied to them. The paper aims to reach the rationale understanding of the norms of modern architecture in Lefkosa in the twentieth century. The methodology is based on analyzing the residential buildings designed by local architects and “Ahmet Vural Bahaeddin” selected as one of the famous modernist architects in the twentieth century in North Cyprus. Residential buildings from Milan and Rome in Italy, as well as Barcelona in Spain, selected for analysis. The paper tries to demonstrate the presence of vernacular elements in modern architecture in Lefkosa. Two vernacular elements were studied, i) the patio (outside and inside interrelation), and ii) the façade materials (exposed stone) as vernacular elements in “Mediterranean modernist architecture”. The paper delineated the influence of the “Mediterranean modernist movement” on modern architecture in Lefkosa in the 20th century. The findings show that there is influence by the Modernist movement of architecture in other Mediterranean cities in Italy and Spain on the modern architecture in Lefkosa. The results contribute evidence to promote our understanding regarding the modernist architecture in Lefkosa.